DINAMIKA BAHASA BAKU DI ERA DIGITAL - Elzi Rahma Liza; Firna Yulia Amanda; Fitria; Hapsah Zani Adawiyah; Farel Olva Zuve (UNIVERSITAS PGRI YOGYAKARTA, 2026)
This study examines the dynamics of standard language use in the digital era by exploring public perceptions, attitudes, and linguistic practices across formal, social, and digital contexts. Technological developments and digital culture have increased the use of non-standard language, including slang, abbreviations, and code-mixing, which may affect the stability of standard language as a national identity marker. This research aims to analyze how digital communication shifts influence the sustainability of standard Indonesian and what strategies can be implemented to preserve it. Using a descriptive qualitative method through literature review, digital content analysis, and questionnaires, the findings reveal that most respondents hold positive perceptions of standard language and consider it essential in academic, professional, and formal communication settings. However, standard language use becomes more flexible in digital platforms that encourage informal and expressive communication styles. Despite this shift, there is collective awareness of the need to preserve standard language through education and enhanced language literacy across digital media. The study concludes that although digital culture impacts linguistic behavior, standard Indonesian remains significant and must be maintained through continuous language development efforts and adaptive policy strategies.